Exploring the Effectiveness of Web Crawlers in Detecting Security Vulnerabilities in Computer Software Applications - Biao Wan; Chunmei Xu; Jahoon Koo (International Journal of Informatics and Information Systems, 2023)
With the rapid development of the Internet, the World Wide Web has become a carrier of a large amount of information. In order to effectively extract and use this information, web crawlers that crawl various web resources have emerged. The interconnectedness, openness, and interactivity of information in the World Wide Web bring great convenience for information sharing to the society and they also bring many security risks. To protect resource information, computer software security vulnerabilities have become the focus of attention. This article is based on the method of computer software security detection under a web crawler simply analyzes the basic concepts of computer software security detection and analyzes the precautions in the process of security detection. Finally, combined with the computer software security vulnerability problems in the web crawler environment, its security detection technology Application for further analysis.